2019
DOI: 10.1371/journal.pone.0223356
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen nutrition is a key modulator of the sugar and organic acid content in citrus fruit

Abstract: ‘Huangguogan’ (Citrus reticulata × C. sinensis) is a new cultivar of mandarin citrus in China, and the research on fertilization of ‘Huangguogan’ is very limited. In this study, the effect of N fertilization on ‘Huangguogan’ fruit quality was determined at ripening. Sugars (sucrose, fructose, and glucose), organic acids (pyruvic, oxalic, citric acid, etc.), and vitamin components were measured at six stages of fruit development, and eight enzymes related to the glycolytic and Krebs cycle were assessed. The 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 66 publications
(71 reference statements)
0
24
0
1
Order By: Relevance
“…Sugar is the ultimate precursor for most quality-relevant components in the fruit of bananas, such as acids, pigments, tannins, and aroma volatiles (Hall et al, 2011 ). A high acid content often reduces fruit quality, though a moderate concentration of acid can improve the palatability of fruits (Liao et al, 2019 ). Therefore, the quality of a fruit and its taste are usually influenced by the sugar and acid contents or, more simply, by its sugar-to-acid ratio (Qiao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar is the ultimate precursor for most quality-relevant components in the fruit of bananas, such as acids, pigments, tannins, and aroma volatiles (Hall et al, 2011 ). A high acid content often reduces fruit quality, though a moderate concentration of acid can improve the palatability of fruits (Liao et al, 2019 ). Therefore, the quality of a fruit and its taste are usually influenced by the sugar and acid contents or, more simply, by its sugar-to-acid ratio (Qiao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a high amount of N and P in the rhizosphere soil of plants amended with compost and inoculated with AMF and PGPR could be due to a direct absorption via compost or by the fact that AMF and PGPR efficiently and directly take up from the soil to the plant nutrients such as N and P (Grobelak et al, 2015;Liu et al, 2018). In order to tolerate drought stress, plant adaptation is associated with high concentration of solutes such as soluble sugars and protein to regulate the osmotic potential of cells which, in turn, induce an improvement in water absorption under unfavorable condition (Zhang et al, 2010;Liao et al, 2019). Our data indicated that the concentrations of soluble sugars and protein in leaves increased during drought stress in treated plants as compared to microbes-free controls.…”
Section: Discussionmentioning
confidence: 99%
“…In order to tolerate salt stress, plant synthesizes a high concentration of compatible carbohydrates like protein and soluble sugars, which are able to increase intracellular osmotic (Liao et al 2019). They play a crucial role in enzyme and membrane protection from adverse effect of stress (Hare et al 1998).…”
Section: Discussionmentioning
confidence: 99%